2019
DOI: 10.4209/aaqr.2019.08.0410
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Health Risk of PM2.5 from Near-ground Firecracker Burning in Micro Region of Eastern Taiwan

Abstract: The randomness of firecracker-burning site and the overlapping impact of multi-sources makes the source apportionment of PM 2.5 during the firecracker burning events more difficult. To investigate the influences of the downwind distance to the firecracker-burning site on the temporospatial distribution of PM 2.5 and public health risk, PM 2.5 were sampled at three sites adjacent to a fixed firecracker-burning route accompanied with annual pilgrimage activity during the Lantern Festival in Taitung, Taiwan, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…To date, there have been some studies of PM 2.5 variation with firework displays, but most of the works have focused on individual cities [ 40 , 42 , 45 , 48 , 49 , 89 ]. However, considering that China has a large span of latitude and longitude, the climatic characteristics and geographical conditions are quite different, which makes the researches based on a single city have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been some studies of PM 2.5 variation with firework displays, but most of the works have focused on individual cities [ 40 , 42 , 45 , 48 , 49 , 89 ]. However, considering that China has a large span of latitude and longitude, the climatic characteristics and geographical conditions are quite different, which makes the researches based on a single city have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the cultural meaning of fireworks in the Chinese New Year celebration, high-intensity displays are common, and the firework contribution to air pollution is considerable [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. It has been reported that during the seven days of celebration following the Chinese Lunar New Year’s Eve in 2013, up to 5505 tons of firework residues were removed from the streets in Beijing [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ionic composition on Hualien leaves was dominated by sea salt (Na, Cl), reflecting the small distance to the sea (50 km in the main wind direction). Nitrate and sulfate are mainly composed of secondary ammonium sulfate and ammonium nitrate from industry (Yang et al, 2017 ; Shen et al, 2019 , 2020 ). Nitrate, ammonium, and potassium strongly contributed to the composition of particles on Pingtung leaves, whereas the sulfate and magnesium concentrations were higher on Hualien leaves ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…Particulate matters (PMs) are a complex mixture of organic and inorganic substances that are suspended in air, which consists of sulfates, nitrates, ammonia, sodium chloride, black carbon, mineral dust, and water (WHO, 2016). PMs are classified according to their morphology and elemental composition as geogenic, anthropogenic, and biogenic aerosols usually obtained from vehicular emissions, biomass burning, re-suspended road/soil dust (Zeb et al, 2018), firecracker burning, and kitchen fumes (Shen et al, 2019). Several other factors such as relative humidity, seasonal change, and transboundary pollution can also contribute to the levels of PMs in the environment (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%